Effect of Palliative Bronchoscopic Interventions on Symptom Burden in Patients with Central Airway Narrowing: A Retrospective Review - Pandit, Anuja (Indian J Palliat Care, 2019)
INTRODUCTION: Early integration of palliative interventions in patients with central airway obstruction (CAO) has shown to reduce patients' distress due to breathlessness and achieve better outcomes at lower cost. This retrospective review was performed to determine whether rigid bronchoscopic interventions alleviated the symptom burden and the requirement for continued mechanical ventilation in patients with CAO in a tertiary care hospital. MATERIALS AND METHODS: Detailed records of 105 patients with CAO were retrospectively studied. The Numerical Rating Scale (NRS) score for cough and dyspnea before and after the intervention was noted. A need for an escalation or reduction in level of care was also noted. RESULTS: The mean NRS score for dyspnea (n = 84) reduced from 7.5 (4–9) (before procedure) to 2.5 (2–6) after intervention (P < 0.01). The mean NRS score for cough (n = 68) also reduced from 6.5 (4–8) (before procedure) to 4 (3–7) after intervention (P < 0.01). Of these patients, bronchoscopic intervention allowed transfer out of the ICU in 14 patients (42%) and immediate withdrawal of mechanical ventilation in 8 patients (42%). CONCLUSION: There is an instantaneous valuable palliation of symptoms and improved health-care utilization with airway tumor debulking and stenting. Multidisciplinary interventions with emphasis delivery of palliative care provide better care of patients with CAO.